2016
DOI: 10.1039/c6dt02474b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring electronic effects on the partitioning of actinides(iii) from lanthanides(iii) using functionalised bis-triazinyl phenanthroline ligands

Abstract: The first examples of 4,7-disubstituted 2,9-bis(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-1,2,4-benzo-triazin-3-yl)-1,10-phenanthroline (CyMe-BTPhen) ligands are reported herein. Evaluating the kinetics, selectivity and stoichiometry of actinide(iii) and lanthanide(iii) radiotracer extractions has provided a mechanistic insight into the extraction process. For the first time, it has been demonstrated that metal ion extraction kinetics can be modulated by backbone functionalisation and a promising new CHON complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Only ah andful of neutral ligandst hat exhibit high selectivity for light lanthanides in solvent extraction systems have been previously described. [5][6][7][8] Them ajorityo ft he known ligandse xhibit the reverse trend, that is, by being more selectivet owardsh eavy lanthanides.E xamples include acidic compounds, such as bis(2-ethylhexyl) phosphoric acid (D2EHPA), [9] am ixture of phosphinica nd phosphonic acids (Cyanex572) [10] and bis(2ethylhexyl)phosphinic acid, [11] and neutral compounds, [12] such as N,N,N',N'-tetraoctyldiglycolamide (TODGA), [13][14][15] trialkylphosphine oxides( e.g.,C yanex9 23) [16] and bis-triazinylpyridine, [17][18][19] to mention but afew.…”
Section: Introductionmentioning
confidence: 99%
“…Only ah andful of neutral ligandst hat exhibit high selectivity for light lanthanides in solvent extraction systems have been previously described. [5][6][7][8] Them ajorityo ft he known ligandse xhibit the reverse trend, that is, by being more selectivet owardsh eavy lanthanides.E xamples include acidic compounds, such as bis(2-ethylhexyl) phosphoric acid (D2EHPA), [9] am ixture of phosphinica nd phosphonic acids (Cyanex572) [10] and bis(2ethylhexyl)phosphinic acid, [11] and neutral compounds, [12] such as N,N,N',N'-tetraoctyldiglycolamide (TODGA), [13][14][15] trialkylphosphine oxides( e.g.,C yanex9 23) [16] and bis-triazinylpyridine, [17][18][19] to mention but afew.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of electronic variation of BTPhen on the extraction of An/Ln was studied (Figure 4, right) and showed order-of-magnitude differences in distribution ratios while maintaining a high separation factor (SFAm/Eu ca. 110) [22]. The extraction mechanism was studied for Cm(III) by time-resolved laser-induced fluorescence spectroscopy (TRLFS).…”
Section: Insert Figurementioning
confidence: 99%
“…Only distribution ratios of lanthanides(III) have been reported. [23,[37][38] Higginson et al reported on the application of CyMe 4 BTPhen as extractant in a liquid-liquid extraction process for nuclear forensics application from chloride media [39] and in an immobilized form as Me 4 BTPhen for the same application. [40] They found Cd(II) to be co-extracted by CyMe 4 BTPhen, but didn't test all the fission and activation products present in used nuclear fuel.…”
Section: Experiments Using Simulated Purex Raffinatementioning
confidence: 99%